Populism and Civil Society - Boeri, Tito.; Mishra, Prachi; Papageorgiou, Chris; Spilimbergo, Antonio (Washington, D.C. : International Monetary Fund, 2018)
Populists claim to be the only legitimate representative of the people. Does it mean that there is no space for civil society? The issue is important because since Tocqueville (1835), associations and civil society have been recognized as a key factor in a healthy liberal democracy. We ask two questions: 1) do individuals who are members of civil associations vote less for populist parties? 2)does membership in associations decrease when populist parties are in power? We answer thesequestions looking at the experiences of Europe, which has a rich civil society tradition, as well as of Latin America, which already has a long history of populists in power. The main findings are that individuals belonging to associations are less likely by 2.4 to 4.2 percent to vote for populist parties, which is large considering that the average vote share for populist parties is from 10 to 15 percent. The effect is strong particularly after the global financial crisis, with the important caveat that membership in trade unions has unclear effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet